ANALISIS KESULITAN BELAJAR MENULIS PERMULAAN PADA SISWA KELAS I SD NEGERI X DI INDRALAYA TAHUN 2024/2025 - Jerry Ahmad Khodhori; Indah Permata Sari; Nabila Dwi Putri; Muhammad Ridho Bima Addli; Silvia AR (Jurnal Lensa Pendas, 2025)
Writing skills are fundamental abilities that must be mastered by elementary school students as a foundation for future academic success. This study aims to analyze the early writing skills of first-grade students at SD Negeri x Indralaya Selatan and to identify the factors that influence their writing proficiency. A descriptive qualitative method was used with a sample of 18 students. The research instruments included writing skill tests involving activities such as connecting lines, tracing patterns, free scribbling, copying letters, and writing through dictation. The results showed that most students still faced difficulties with basic writing skills, such as maintaining neat handwriting, forming letters correctly, and accurately following dictation instructions. Several contributing factors were identified, including a lack of focus during learning, weak mastery of the alphabet, and limited fine motor skills. These findings are expected to serve as a foundation for developing more effective and developmentally appropriate writing instruction strategies for early grade students, in order to improve their learning outcomes in the long term.